Efficient co-production of xylooligosaccharides and glucose from lignocelluloses by acid/pentanol pretreatment: Synergetic role of lignin removal and inhibitors. (December 2022) - Madadi, Meysam; Zahoor,; Shah, Syed Waqas Ali; Sun, Chihe; Wang, Wen; Ali, Sameh Samir; Khan, Ahmad; Arif, Muhammad; Zhu, Daochen
Graphical abstract: Highlights: DA/pentanol pretreatment is effective to produce xylooligosaccharides (XOS). High XOS yields of 48.65% (pine sawdust) and 46.85% (wheat straw) were obtained. Lignin removal and low dosage of inhibitors considerably enhanced XOS yield. Solid residues yielded 88.65% (pine sawdust) and 93.34% (wheat straw) glucose. Enlarged pore size significantly increased cellulose digestibility. Abstract: A novel technology for co-production of xylooligosaccharides (XOS) and glucose from Monterey pine sawdust and wheat straw was introduced using dilute acid (DA)/pentanol pretreatment. Effects of pretreatment severity ( PS ), lignin removal, and inhibitors with byproduct concentrations on XOS production were investigated. Optimal identified conditions ( PS : 3.71; 170 °C, 45 min) resulted in maximum XOS of 48.65 % (pine sawdust) and 46.85 % (wheat straw), due to appropriate lignin removal (pine sawdust, 88.5 %; wheat straw, 89.7 %) and formation of small amounts of inhibitors and byproducts. Enzymatic hydrolysis of optimal pretreated solid residues yielded 88.65 % and 93.34 % glucose in pine sawdust and wheat straw, respectively. Biomass characterization revealed that DA/pentanol pretreatment enhanced porosity and pore size along with removal of amorphous fractions in both samples, thereby increasing cellulose accessibility and glucose yield. This study demonstrated lignin removal and low formation of inhibitors and byproducts, effectively enhancing XOS and glucose production from lignocellulosic biomass.